EDUKASI KEAMANAN PANGAN KERANG REBUS DENGAN MEMANFAATKAN BELIMBING WULUH DI KOTA BANDA ACEH - Faridah Hanum; Nurhayati Nurhayati; Dwi Sudiarto; Noni Zakiah; Eka Oktarina Riani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Shell is one of the sources of seafood because it contains protein and minerals. However, shells can accumulate more metals than other aquatic animals. Based on Hanum, F' s research (2017), showed that starfruit juice can eliminate Plumbum content in boiled mussels. This needs to be known by the community from the aspect of chemical safety given the high level of heavy metal pollution in waters in Aceh. The community service activity took place for 2 days at the Balee Pengajian Alue Deah Teungoh Village in Meuraxa District, Banda Aceh. The target activity is 40 residents. Based on the results of the activity it can be concluded that the counseling and demonstration of Plumbum testing has been able to improve the knowledge and skills of participants in the technique of processing boiled mussels as a favorite family snack. Starfruit is very effective to be used as a sequestrant.